Artificial Intelligence in Education: Opportunities and Challenges of AI Integration in Indonesian Classrooms - Annida Herviana (Yayasan Cerdas Pedia Indonesia, 2025)
The integration of artificial intelligence (AI) in educational settings presents unprecedented opportunities for personalized learning and enhanced educational outcomes, yet significant implementation challenges persist, particularly in developing nations like Indonesia. This study examines the current state of AI adoption in Indonesian classrooms, identifying key barriers and opportunities for effective integration. A systematic literature review was conducted utilizing PRISMA guidelines to analyze peer-reviewed articles, government reports, and scholarly publications focusing on AI integration in Indonesian education. Mixed-method approaches combined quantitative analysis of AI adoption rates and educational outcomes with qualitative insights from case studies and stakeholder interviews across diverse Indonesian educational settings. Cross-sectional data highlighted infrastructure, teacher readiness, and digital access disparities between urban and rural regions. The findings reveal significant disparities in AI adoption, with only 15% of Indonesian primary schools integrating AI technologies compared to 25% globally. Infrastructure deficits affect 85% of educational institutions, while teacher training inadequacies impact 81% of institutions. Despite these challenges, properly implemented AI demonstrates substantial positive impacts, with 42% improvement in student engagement, 30% increase in learning outcomes, and 35% enhancement in personalized learning experiences. Five primary barriers were identified: infrastructure deficits, teacher training inadequacies, digital divide disparities, data privacy concerns, and cost constraints. While AI integration faces substantial challenges in Indonesian education, the potential benefits for learning outcomes and educational equity are significant. Success depends on addressing infrastructure limitations, developing comprehensive teacher capacity, and creating supportive policy environments that promote responsible AI implementation through collaborative partnerships between government, educational institutions, and private sector organizations.